Brussels IIbis Regulation. - Magnus, Ulrich; Mankowski, Peter (Walter De Gruyter, 2012)
The Brussels IIbis Regulation is the magna charta of cross-border divorce and cross-border lawsuits concerning parental responsibility in Europe. It has substantially changed the nature of lawyers' advice to clients in such cases. This commentary:- is the first ever English language article-by-article commentary on this very important piece of European legislation, - combines in-depth analysis with a genuine and truly European perspective, authored by top experts from all over Europe, and- provides for necessary guidance, as the European Court of Justice will not be passing guiding judgments in.